The impact of technology in Indigenization strategy - Abass Ali Hamza; Suaad Khaleel Ibrahim; Arwa Mohammed Mubarak (Iraqi Journal of Architecture and Planning, 2017)
The swift development of technology have a major act in architectural project making, which Features by changes and development in the intellectual and formal aspects. It showed the new formal Types of buildings with the zeitgeist of the technical aspects whether it is in the process of design or construction. Many of the architectural projects appeared that carry a formality contemporary values stemming from technology concepts within the context of local architecture, from here research come to study the impact of technology in the process of production the contemporary local architecture. Thus emerged the concept of technological indigenization whichmean (Approach for framing the mechanisms of the project intellectual and physical vocabularythrough available means, skills and mental ability, accommodate contemporary reality and emulatethe spirit of the original towards achieve communication between past, present and future). Researchproblem is lake of knowledge about the relationship between the technology concepts andindigenization strategy in general and types of creation the contemporary local architecture projectin specific. Research aim find a theoretical framework describing the nature of the relationshipbetween the technology concepts and indigenization strategy in the creation the contemporary localarchitecture project. For that research methodology achieved built theoretical framework contentssix vocabulary (mechanisms of technological indigenization strategy, Features of indigenizeprojects, contextual of technological indigenization, layers of technological indigenization, spatial ofindigenize projects and goals of technological indigenization). And the application of these items onthe two projects and then put research and reach final conclusions about how the technologicalindigenization strategy achieve contemporary local architecture.Technology indigenization, features of the text of indigenization, technology indigenization strategies, local architecture